Visual loss and optic nerve head swelling in thiamine deficiency without prolonged dietary deficiency - Gratton SM (Dove Medical Press, 2014)
Sean M Gratton, Byron L LamBascom Palmer Eye Institute, University of Miami, Miller School of Medicine, Miami, FL, USAAbstract: Visual loss due to optic neuropathy is a rare manifestation of thiamine deficiency. We report a case of a 39-year-old woman with a body mass index (BMI) of 29 kg/m2 who developed visual loss and bilateral optic nerve head swelling after a short, self-limited gastrointestinal illness. She was disoriented and inattentive and had absent ankle jerk reflexes, diminished sensation in both legs below the knees, and marked truncal ataxia. Magnetic resonance imaging (MRI) showed increased T2-signal in the medial thalami and mammillary bodies. The serum thiamine level was 8 nmol/L (normal 8–30). The diagnosis of thiamine deficiency was made, and the patient’s vision and neurologic symptoms improved significantly with intramuscular thiamine treatment. Thiamine deficiency can occur in the absence of an obvious predisposing factor such as alcoholism or low body weight. The clinician must be aware of the factors that govern vitamin availability and maintain a high index of suspicion to make the diagnosis in such cases.Keywords: optic neuropathy, nutritional deficiency